Does packaging influence taste and quality perceptions across varying consumer demographics?. (September 2020) - Khan, Huda; Lee, Richard
Highlights: Packaging linguistics have differential effect on taste and quality perceptions. Income and English literacy do not change packaging preference and perceptions. Global packaging leads to greater brand likability. Brand managers of Western brands should offer global packaging in emerging markets. Abstract: This study investigates the important managerial issue of whether the packaging language of the Western consumer packaged-food (CPF) products should be adapted for emerging markets. An experiment using a 2 (Western vs adapted packaging) × 2 (product categories) design was conducted instore with real products to enhance the study's external validity. With Pakistan as the contextual emerging market, Pakistani shoppers (n = 188) were exposed to the English and adapted (Urdu) packaging of the two products, and rated their quality perception, packaging likability, and attributes associated with the packaging. They also tasted and rated their overall satisfaction with the taste, and chose their preferred packaging. Underpinned by standardisation and adaptation literature and symbolic perception theory, the findings show that consumers rated and preferred the English packaging more than the adapted packaging. Also, while the English packaging was associated with attributes including elegance and trustworthiness, the adapted packaging was viewed as more personalised. Furthermore, the findings hold across demographic variables of income and English language literacy. These findings run contrary to the prevailing strategy of Western global brands in emerging markets, where the usual practice is to localise the packaging of the brands as they enter the markets. The findings provide both theoretical and practical insights into the implications of localisation strategy of Western brands in emerging markets.